Efficient Vertical Handoffs in Wireless Overlay Networks - Badis, Hakim; Agha, Khaldoun Al (COMPUTING AND INFORMATICS, 2012)
Mobile IP is used to keep track of location information and make the data available to the mobile device anytime, anywhere. It is designed to address the macro-mobility management, it does not address micro-level mobility issues such as handoff latency and packet loss. In this paper, we propose a mobility management scheme to handle the movements of mobile nodes among different wireless network technologies. Our scheme combines: (a) A hierarchical mobility management architecture to hide mobility of mobile nodes within the foreign domain from the home agent; (b) A handoff protocol to reduce packet loss during the transition from one cell to another; (c) The use of our proposed virtual cells in order to reduce the upward vertical handoff latency and disruption as much as possible. Our design is based on the Internet Protocol (IP) and is compatible with the Mobile IP standard (MIP). We also present simulation results showing that our handoff scheme is very fast to meet the requirements of an interactive communication session such as Internet telephony and avoiding packet loss.